Peculiarities of immune system functioning of patients with endometrium cancer depending on the tumor differentiation grade - A. I. Pashov; V. B. Tskhai; N. I. Kamzalakova; L. N. Platonova (Бюллетень сибирской медицины)
The aim of investigation is to define the peculiarities of immune system functioning of patients with endometrium cancer depending on the tumor differentiation grade. 133 female patients of comparable age in menopause have been examined: healthy women, patients with histological verified high-, medium- (1-st group) and low-differentiated (2-nd group) endometrium adenocarcinoma of the I stage. Estimation of the immune state has been made in accordance with generally accepted recommendations. Immune system activation has been stated in the 1-st group, in the 2-nd group there has been marked a dissociation of the function of basic immune system chains and a decrease of their functional abilities.